Glucose and insulin homeostasis during the Jarisch-Herxheimer reaction - Teklu, B; Habte-Mlchael, A; White, N; Warrell, D; Wright, D; Turner, R (1985)
Plasma concentrations of glucose and insulin were measured in ten patients during the Jarisch-Herxheimer reaction of tetracycline-treated louse-borne relapsing fever. Plasma glucose fell significantly in eight of the ten patients associated with the peak of the reaction, but plasma insulin remained low. Glucoregulation by insulin was therefore normal. This evidence questions the role of macrophage mediator-induced pancreatic insulin release in causing hypoglycaemia in borreliosis or bacterial endotoxicosis. © 1985.